Visitor

2015-10-24 13:33:33

#1

Prove that f: R-> R, F (x) = (x-1) e^{x} is primitive of the function f:R->R,f(x)=xe^{x}

Visitor

2015-10-24 13:36:39

#2

If F is a primitive of * f* then F`(x)=f(x).

F'(x)=(x-1)'•ex+(x-1)•(ex)'=ex+(x-1)•ex=x•ex

F'(x)=(x-1)'•ex+(x-1)•(ex)'=ex+(x-1)•ex=x•ex

It is not mandatory to be logged in on this forum but it is nice to have an account. You can ask about mathematics just with your name and your email.

This maths forum is one of the easiest forums to use it.